APLIKASI SISTEM PELAPORAN TANDA BUKTI TRANSAKSI PADA PT. POS INDONESIA CABANG MRANGGEN - Bukhori Bukhori; Dani Sasmoko (Pusat Riset dan Inovasi Nasional, 2024)
At PT. Pos Indonesia Mranggen Branch in making transaction receipt reports so far still uses Microsoft Excel where there are many columns in it, so that in its operation it still confuses users in this case are employees who work at the branch office. The purpose of this research is to assist employees in completing the work of making reports related to transaction reporting. In the process of collecting data with the aim of solving problems, the authors use descriptive data collection methods, namely by observation and interviews. And to design the software application, the writer uses Access Database 2007 and Visual Basic 6.0 Application, while the report system uses Crystal Report 8.5 Application. The final result of this research is a Transaction reporting system application that can provide convenience for employees in entering (input) transaction reporting data where there are several forms that are very easy to operate that no longer use many columns in it.